381 Evaluation of the international classification of functioning, disability and health for assessing disability of the brazilian national social security institute. (24th April 2018) - Ferreira, LR; Capeli, VASB; Fregonesi, RL; Lemos, AFA; Galhardi, CM
Abstract : Introduction: The assessment of the person with disabilities can be made by using the ICF (International Classification of Functioning, Disability and Health). It has been used by the Brazilian National Social Security Institute (INSS) to concede the Social Security Continuous Benefit (BPC) for disabled person, and it evaluates incapacity for work and independent life. This study analysed the results of the ICF used by the social security medical examiners and social workers on the evaluation of disabled person. Methods: This was a retrospective study involving the evaluation of 173 BPC applicants of the INSS in Brazil from March to December 2016 and collected the following data: average scores from 0 to 4 (0-no disability, 1-mild, 2-moderate, 3-severe, 4-complete disability) for these ICF domains: environmental factors and activities/participation made by the social worker, body functions and activities/participation made by the medical examiners and the final results for granting or not the benefit. It was applied the statistical test of Kruskal-Wallis, the post test of Dunn (p<0.05). Results: The results revealed that 71.1% of the concessions were denied and 28.9% were granted. It was showed divergent values between the medical evaluation with lower values (mean scores of 0.4) in the activity/participation domain compared with results of higher values obtained from the social assistants (mean scores of 3.0) for the same domain. These results were statistically significant with p<0.001. Discussion: The results were divergent when comparing the evaluations made by the medical examiners and social workers. These results may help assist in a better understanding of the analysis of the ICF as an instrument for the evaluation of BPC. It is suggested the need of possibly better standardisation in the method of the ICF instrument application in order to minimise the divergence of results